The Effect of Ethnomathematics-Based LKPD Using Kite Context on Students’ Learning Outcomes in Lines and Angles - Afifah Nabila Nasution; Muhammad Nuh (Juring (Journal for Research in Mathematics Learning), 2026)
This study investigates the effect of an ethnomathematics-based LKPD using a traditional kite context on students’ learning outcomes in the topic of lines and angles. The study employed a quasi-experimental design with a pretest–posttest control group design. The sample consisted of 64 students divided into an experimental group and a control group, selected through cluster random sampling. The research instrument was a multiple-choice test consisting of 20 valid and reliable items (Cronbach’s Alpha = 0.836). Data were analyzed using descriptive and inferential statistics, including an independent samples t-test. The results showed that the mean score of the experimental group increased from 35.31 (pretest) to 83.75 (posttest), while the control group improved from 35.00 to 74.06. The independent samples t-test revealed a statistically significant difference between the two groups (t = 3.087, p = 0.003). Furthermore, the effect size analysis using Cohen’s d yielded a value of 0.77, indicating a moderate to large effect. In conclusion, the ethnomathematics-based LKPD using a kite context has a significant and meaningful effect on improving students’ learning outcomes in learning lines and angles.